Preparative Treatment with Naoh to Selectively Concentrate Iron Oxides of a Chilean Volcanic Soil Material to Produce Effective Heterogeneous Fenton Catalyst - Rubio-Campos, M; Pizarro-Arriagada, C; Pizarro-Arriagada, C (2011)
A Chilean volcanic Ultisol material was first size-fractionated so as to obtain the fraction with mean particle sizes ? < 53 ?m. This sample was then sequentially treated three or five times with 5 mol L-1 NaOH, in an attempt to evaluate the effectiveness of the selective chemical dissolution to concentrate iron oxides, as a preparation procedure before using the materials as heterogeneous Fenton catalysts. The effects of those treatments on the iron oxides mineralogy were monitored with Mössbauer spectroscopy. The NaOH-treated samples were tested as catalysts towards the H2O2 decomposition. Three or five sequential NaOH treatments were found to be comparably effective, by concentrating nearly the same proportion of iron oxides in the remaining solid phase (25.1 ± 0.4 and 23.3 ± 0.2 mass%, respectively). 298 K-Mössbauer patterns were similar for both samples, with a central (super)paramagnetic Fe3+ doublet and a broad sextet, assignable to several closely coexisting magnetically ordered forms of iron oxides. Despite of this nearly similar effect of the two treatments, the Ultisol material treated three times with NaOH presents higher heterogeneous catalytic efficiency and is more suitable to decompose H2O2 than that with five treatments. © 2011 Springer Science+Business Media B.V.